Comparisons between different blood pressure measurement techniques in patients with chronic kidney disease - Shahrokh Ezzatzadegan Jahromi; Ghasem Haghighi; Jamshid Roozbeh; Vahid Ebrahimi (Kidney Research and Clinical Practice, 2019)
Background : Automated office blood pressure (AOBP) machines measure blood pressure (BP) multiple times over a brief period. We aimed to compare the results of manual office blood pressure (MOBP) and AOBP methods with ambulatory BP monitoring (ABPM) in patients with chronic kidney disease (CKD).